Genetic counseling research and COVID‐19: A lesson in resiliency. Issue 5 (12th September 2021) - Borle, Kennedy; Dey, Alivia; Carrion, Prescilla; Austin, Jehannine; Elliott, Alison M.
Abstract: GenCOUNSEL is the largest genetic counseling research grant awarded to date and brings together experts in genetic counseling, genomics, law and policy, health services implementation, and health economics research. It is the first project of its kind to examine the genetic counseling issues associated with the clinical implementation of genome‐wide sequencing (exome and genome sequencing). GenCOUNSEL is a Canadian‐based, multi‐method research study that takes place over a variety of sites, including non‐clinical, clinical, and laboratory research sites and includes the training of undergraduate and graduate students. The COVID‐19 pandemic will likely have a lasting impact on genetic counseling service delivery, research, and training. Almost every aspect of the GenCOUNSEL research project has been impacted by the COVID‐19 pandemic. Here we describe how our research recruitment strategies, methods, resource allocation, and training capacity have been affected. We discuss ways that we have adapted to the pandemic including revision of our research methods and work to understand the barriers in order to optimize opportunities. We finish with take‐home messages to fellow researchers highlighting the importance of resiliency in genetic counseling research.